ANALISIS LOYALITAS KONSUMEN TERHADAP RETAIL STORE DI BOGOR - Hartati, Lesti; Dharmmest, Basu Swastha (Universitas Pakuan, 2011)
ABSTRACT This research was designed to achieve the objective of measuring the influence of consumer expectation and retail marketing mix on store loyalty and store image which are mediated by customer satisfaction. Four hypotheses describing the influence of those variables have been tested using regression analysis. Primary data were collected using a questionnaires from sample respondents of Giant Hypermarket consumers in Bogor. The instrument has been tested to measure construct validity and reliability, confirmatory factor analysis and Cronbach Alpha methods were used. This research also tested the role of consumer satisfaction as a mediating variable between consumer expectation and retail marketing mix on the one hand and store loyalty and store image on the other hand. The results show that consumer satisfaction is justified as a full mediator and partial mediator. Implications and limitations are also presented. Key words: customer expectation, retail marketing mix application, customer satisfaction, store loyalty, store image, retail consumer.